Implementation of Total Quality Management on Nurse Performance and Quality of Nursing Services - Yuliyanti Yuliyanti; Tri Kurniati; Giri Widakdo (UIMA Press, 2024)
Background: Performance and quality of nursing services are quite essential in healthcare services. Sustainable improvement of the healthcare service system must be conducted frequently to maintain the good quality of healthcare services. One of the approaches that can be utilized is the implementation of Total Quality Management. The aim of this study is to determine the relationship between the implementation of Total Quality Management towards the performance and quality of nursing services. Objectives: This study aims to determine the relationship between the implementation of Total Quality Management with nurse performance and the quality of nursing services. Methods: This type of research is a quantitative research which employed correlation study where the sample of 196 nurses were taken by using stratified random sampling technique with finite population calculation. Results: The study shows a significant correlation between the implementation of Total Quality Management and nurse performance and the quality of nursing services (p-value 0.000 > 0.005) Conclusion: The implementation of Total Quality Management with 33.9 (95% CI 23.6 - 44.7) OR is identified as the most dominant and influential variable towards nurse performance controlled by variables of degree of education, gender, and age. Meanwhile, variable of degree of education with 5.04 (95% CI 1.32 - 6.52) OR is found as the most dominant and influential variable on the quality of nursing services. Keywords: Nurse Performance, Service Quality, Total Quality Management